Strengthening Digital Transformation of Mass Media for National Resilience - Winarko, Heru; Avianto, Lucky (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study examines the digital transformation of Indonesia's mass media and its critical impact on national resilience, focusing on both the opportunities and challenges arising from this transition. Study Design/Methodology/Approach: Adopting a qualitative descriptive approach with secondary data analysis, this study utilizes a PESTLE-SWOT framework to assess the role of digital media in bolstering Indonesia’s information infrastructure, human resource development, and regulatory frameworks that are essential for maintaining national security. Findings: The findings reveal that while digital transformation improves information accessibility and efficiency, it also introduces significant challenges. These include increased risks of misinformation, fragmented regulations, and disparities in digital infrastructure across regions. Such disparities especially impact remote areas, exacerbating information inequality. To counter these issues, a coordinated policy approach, equitable infrastructure development, and enhanced digital literacy initiatives are necessary to strengthen resilience. Originality/Value: This study underscores the strategic importance of an integrated policy framework to leverage digital media for national resilience, recommending strengthened regulations and equitable digital infrastructure to mitigate security risks and foster inclusive information access.